A phenomenological perspective of science diplomacy of India and assessing STI policies - Pooja Raghav; Trishna Rai (Cogent Social Sciences)
Advancements in science and the increasing globalisation of international issues are pushing scientific endeavours toward new frontiers. This can be observed particularly at the forefront of diplomacy. Due to the complexity of international relations and emerging global challenges, most developed nations are trying to incorporate science into their foreign policies. Science diplomacy in emerging economies, particularly in South Asia where scientific and technological advancements are driven by nations like India, remains a largely unexplored area of research. This paper contributes to a deeper understanding of India’s significant growth in science diplomacy through three foci: access, promotion and influence. The significant growth and issues surrounding science policy in India are highlighted. A phenomenological perspective with a single case study research methodology is used to gain accurate understanding of science diplomacy in India. Policy documents review and semi-structured interviews were conducted with 9 relevant actors it concludes with India’s stand on science diplomacy as an emerging economy and points to the significance of Track II diplomacy actors. India being a developing nation lack complete awareness of science diplomacy. However, there is a need to spread awareness about science diplomacy to increase its practical use in the policy formulations and implementation.